(untitled) (Journal of Health, Population and Nutrition, 2010)
Vibrio cholerae is a major cause of diarrhoeal illness in endemic regions, such as Bangladesh. Understanding the factors that determine an individual’s susceptibility to infection due to V. cholerae may lead to improved prevention and control strategies. Increasing evidence suggests that human genetic factors affect the severity of V. cholerae-associated infection. This study, therefore, sought to characterize the heritable component of susceptibility to infection due to V. cholerae using the Matlab Health and Demographic Surveillance System database of the International Centre for Diarrhoeal Disease Research, Bangladesh. In total, 144 pedigrees that included a cholera patient and 341 pedigrees without a cholera patient were evaluated during 1 January-31 December 1992. The odds of the sibling of a patient being admitted with cholera were 7.67 times the odds of the sibling of an unaffected individual being admitted with cholera [95% confidence interval (CI) 2.40-24.5, p<0.001], after adjustment for gender, age, socioeconomic status, and hygiene practices. Although exposure to environmental reservoirs is essential in the epidemiology of cholera, household-specific factors, such as familial relatedness to an index case, may also be important determinants of risk of cholera. Further analysis of human genetic factors that contribute to susceptibility to cholera may be productive. Key words: Case-control studies; Cholera; Familial aggregation; Risk factors; Vibrio cholerae; Bangladesh DOI: 10.3329/jhpn.v27i6.4324 J Health Popul Nutr 2009 Dec; 27(6): 733-738